Judicial Concept Acquisition: An Analytic Framework - Anthony Connolly (UCL Journal of Law and Jurisprudence, 2015)
Drawing on contemporary trends in analytic and naturalistic philosophy of mind, this paper sets out to provide a theoretical account of the cognitive and practical process by which new concepts are acquired by judges over the course of a legal hearing. It also aims to discern the factors which condition the success or failure of that process and to provide a clear and sound framework for identifying, critically reflecting upon and reforming those aspects of the normative regime presently regulating legal hearings which facilitate or obstruct that process. Read more